2013
DOI: 10.1080/09658211.2013.826673
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thematic congruency, typicality and divided attention on memory for radio advertisements

Abstract: We examined the effects of the thematic congruence between ads and the programme in which they are embedded. We also studied the typicality of the to-be-remembered information (high- and low-typicality elements), and the effect of divided attention in the memory for radio ad contents. Participants listened to four radio programmes with thematically congruent and incongruent ads embedded, and completed a true/false recognition test indicating the level of confidence in their answer. Half of the sample performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 54 publications
3
8
1
Order By: Relevance
“…In previous studies, more hits and false alarms were found with high‐typicality elements, but better accuracy (measured with either d ′ or A ′) was found with low‐typicality elements. These results have been replicated in many different settings: in memory for rooms (Lampinen, Copeland, & Neuschatz, ), in a lecture (Neuschatz, Lampinen, Preston, Hawkins, & Toglia, ), in memory for political arguments (Schmidt & Sherman, ), and in memory for radio ads (Martín‐Luengo et al, , ). Lower accuracy for high‐typicality elements is explained by the fact that they are part of the schema.…”
Section: Memory For Advertisements In Three Types Of Mediamentioning
confidence: 80%
See 4 more Smart Citations
“…In previous studies, more hits and false alarms were found with high‐typicality elements, but better accuracy (measured with either d ′ or A ′) was found with low‐typicality elements. These results have been replicated in many different settings: in memory for rooms (Lampinen, Copeland, & Neuschatz, ), in a lecture (Neuschatz, Lampinen, Preston, Hawkins, & Toglia, ), in memory for political arguments (Schmidt & Sherman, ), and in memory for radio ads (Martín‐Luengo et al, , ). Lower accuracy for high‐typicality elements is explained by the fact that they are part of the schema.…”
Section: Memory For Advertisements In Three Types Of Mediamentioning
confidence: 80%
“…However, this result was not confirmed. Previous work also using laboratory methodology found a benefit in memory for thematically incongruent ads (Furnham et al, ; Martín‐Luengo et al, ; Strick, van Baaren, Holland, & van Knippenberg, ). However, in Experiment 1, there was no improvement in memory by embedding ads into thematically congruent or incongruent programmes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations